An Extensive Coverage Anoa Distribution Modelling in Sulawesi Using Maximum Entropy - Lalu Muhamad Jaelani; Benedict; Diah Ardiani; Mangapul Parlindungan Tambunan; Mochamad Indrawan; Andri A. Wibowo (HAYATI Journal of Biosciences, 2023)
As an endangered species, Anoa (Bubalus depressicornis and Mountain Bubalus quarlesi) inhabiting the Sulawesi island requires proper conservation both in and out of their native habitat. The study of anoa habitat is mainly conducted through field studies based on firsthand observations of anoa appearance, footprints, or excrement or through social surveys from residents who saw it directly. The studies are carried out specifically in a particular area with a relatively narrow. However, in practice, this method has limitations, such as the research location determined based on the possibility of anoa, limited research area, and inefficient use of resources. Therefore, this study aimed to model the potential habitat of anoa in the whole of Sulawesi island. This study was based on physical and environmental independent variables such as DEM, surface slope, LST, NDVI, and access to inland water, as well as in-situ species distribution retrieved from scientific papers and reports. This study discovered the likely anoa distribution on Sulawesi island, both inside and outside of its native habitat. LST is the most important independent variable in determining habitat suitability, accounting for 80% of the total, followed by water (15.3%), NDVI (2.9%), DEM (1.6%), and slope (0.3%).